Avoidant symptoms in PTSD predict fear circuit activation during multimodal fear extinction - Sripada, Rebecca K.; Garfinkel, Sarah N.; Liberzon, Israel (Frontiers in Human Neuroscience, 2013)
Convergent evidence suggests that individuals with PTSD exhibit exaggerated avoidance behaviors as well as abnormalities in Pavlonian fear conditioning. However, the link between the two features of this disorder is not well understood. In order to probe the brain basis of aberrant extinction learning in PTSD, we administered a multimodal classical fear conditioning/extinction paradigm that incorporated affectively relevant information from two sensory channels (visual and tactile) while participants underwent fMRI scanning. The sample consisted of fifteen OEF/OIF veterans with PTSD. In response to conditioned cues and contextual information, greater avoidance symptomatology was associated with greater activation in amygdala, hippocampus, vmPFC, dmPFC, and insula, during both fear acquisition and fear extinction. Heightened responses to previously conditioned stimuli in individuals with more severe PTSD could indicate a deficiency in safety learning, consistent with PTSD symptomatology. The close link between avoidance symptoms and fear circuit activation suggests that this symptom cluster may be a key component of fear extinction deficits in PTSD and/or may be particularly amenable to change through extinction-based therapies.